Evolution of a taboo: pigs and people in the Ancient Near East - Price, Max D. ca. 20./21. Jh. (Oxford scholarship online, 2020)
From their domestication to their taboo, pigs and their shifting roles in the ancient Near East are among the most complicated topics in archaeology. Rejecting monocausal explanations, this text adopts an evolutionary approach and draws upon zooarchaeology and ancient texts to unravel the cultural significance of swine from the Paleolithic to today.